2020
DOI: 10.3390/ijerph17082798
|View full text |Cite
|
Sign up to set email alerts
|

Personal Safety during the COVID-19 Pandemic: Realities and Perspectives of Healthcare Workers in Latin America

Abstract: Healthcare workers exposed to coronavirus (COVID-19) may not have adequate access to personal protective equipment (PPE), safety procedures, and diagnostic protocols. Our objective was to evaluate the reality and perceptions about personal safety among healthcare workers in Latin America. This is a cross-sectional, online survey-based study administered to 936 healthcare professionals in Latin America from 31 March 2020 to 4 April 2020. A 12-item structured questionnaire was developed. A total of 936 healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
1
69

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(238 citation statements)
references
References 4 publications
7
161
1
69
Order By: Relevance
“…Gloves 111(31%), facemasks 98(27.4%), goggles 57(15.9%), gowns/ apron 51(14.2%), and shoe 41(11.5%) PPE were available. The availability of PPE in north Shewa zone hospitals was much lower than a study conducted in Latin America which revealed that gloves (91.1%), gowns (67.3%), face masks (83.9%), and N95 masks (56.1%) (14). This might be due study time which was done early that health care providers could be conscious to use PPE and socioeconomic difference.…”
Section: Availability Of Personal Protective Equipmentmentioning
confidence: 74%
“…Gloves 111(31%), facemasks 98(27.4%), goggles 57(15.9%), gowns/ apron 51(14.2%), and shoe 41(11.5%) PPE were available. The availability of PPE in north Shewa zone hospitals was much lower than a study conducted in Latin America which revealed that gloves (91.1%), gowns (67.3%), face masks (83.9%), and N95 masks (56.1%) (14). This might be due study time which was done early that health care providers could be conscious to use PPE and socioeconomic difference.…”
Section: Availability Of Personal Protective Equipmentmentioning
confidence: 74%
“…A sense of security during a pandemic is also enhanced by a well-prepared workplace, especially healthcare workers. According to the studies by Delegrado et al [ 55 ] conducted among medical staff in Latin America, HCWs had limited access to personal protective equipment, and health authorities support during the COVID-19 pandemic, which may have affected their sense of security. Unfortunately, the authors of the study did not find studies evaluating the sense of security of medical personnel during the COVID-19 pandemic in the literature, so this is the first study to evaluate this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Koh et al [13] conducted a qualitative interview schedule and attained that suffering from the infectious diseases, such as, would signi cantly impact the nurses' risk perception. The latest study of Diego et al conducted in Latin American HCWs showed HCWs perceived limited access to protective equipment and supports, which indicated the organizational safety were also added to the epidemic-related risk for HCWs [14].…”
mentioning
confidence: 99%